Carbohydrate metabolism in insulin resistance: glucose uptake and lactate production by adipose and forearm tissues in vivo before and after a mixed meal. - Coppack, S; Fisher, R; Humphreys, S; Clark, M; Pointon, J; Frayn, K (1996)
1. To examine whether insulin resistance in vivo is manifest equally in both muscle and adipose tissues, we measured arteriovenous glucose and lactate fluxes across forearm (muscle) and abdominal subcutaneous (adipose) tissue in nine obese, glucose-intolerant subjects and 13 non-obese subjects of similar age and sex. 2. Compared with non-obese subjects, the forearm of the obese subjects was resistant to insulin stimulation of glucose uptake after a mixed meal. In contrast, adipose tissue showed little evidence of insulin stimulation of glucose uptake, and adipose tissue in subjects in both normal and obese groups behaved very similarly (assessed per 100 g of tissue). 3. For lactate flux, adipose tissue behaved very similarly (per 100 g of tissue) in obese and non-obese subjects, and was a consistent lactate exporter. 4. We conclude that insulin resistance of glucose uptake observed in the forearm of obese subjects is not evident in adipose tissue. Adipose tissue glucose uptake in obese, insulin-resistant subjects is similar to that in lean control subjects, although it occurs at elevated circulating insulin and glucose concentrations.